Financial Education Programme (Institutional Knowledge at Singapore Management University, 2000)
Associate Professor Tsui Kai Chong, Dean of the School of Business, with Singapore Management University undergraduates at a talk by Sunil Sreenivasan, Citibank's country corporate officer. The talk is part of a financial education programme, supplementary to the SMU core curriculum, which provides practical lessons in finance, banking and economics.